Pelatihan Pemanfaatan Limbah Sagu Sebagai Bahan Pembuatan Pupuk Organik dengan Bioreaktor Bsfl pada Kelompok Tani “Dwitrap” Kampung Tambat Kabupaten Merauke - Yosefina Mangera; Jamaludin Jamaludin (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The Dwitrap farmer group's sago processing industry in Tambat Village produces sago starch/sago flour products. Apart from producing its main product, the sago processing process also produces side products in the form of solid waste and liquid waste. Waste if not handled properly will have a negative impact on the environment. Solid waste from sago processing is in the form of sago dregs. Solid waste from the sago industry contains 56.86% cellulose and 37.70% lignin. Solid waste if disposed of and left unchecked will cause environmental problems such as odor and increased soil acidity (pH<4) which has an impact on inhibiting growth and even causing death in plants. Therefore, proper handling and management of sago industrial waste is needed to reduce the impact on the environment. The content in sago pulp waste is very useful for various purposes such as animal feed and raw material for making organic fertilizer both solid and liquid. Sago solid waste organic fertilizer can be used by the community as a safe fertilizer for plants in community gardens and also BSF larvae can be used as livestock and fish feed. In addition, the purpose of this activity is to provide knowledge to the community about the impact of waste generated and to provide skills in utilizing waste to make it more economical. The method used to achieve this target is socialization about the impact of sago waste and its potential utilization, training or hands-on practice in making liquid organic fertilizer using black soldier fly larvae bioreactor, activity evaluation, and community assistance. The results of the socialization show that there is a transfer of knowledge to the community. This is indicated by the number of questions asked by the participants to the presenters. After the presentation, the presenter gave feedback questions about the material and training that had just been carried out and the participants were able to answer them appropriately. This indicates an increase in public knowledge about the importance of processing sago waste into organic fertilizer, both solid and liquid. This understanding is important so that awareness arises about the importance of preserving the environment and the sustainability of agriculture in the future. In addition, the training also added new skills to the community, namely that the community could produce both solid and liquid organic fertilizer from kitchen waste and solid sago waste with a simple method.